Atomistic simulation of the collective carbon motion in body-centered tetragonal iron: A new insight into the martensite ageing. (1st May 2023) - Huang, Liangzhao; Maugis, Philippe
Abstract: Thermodynamic and kinetic properties of carbon (C) atoms in body-centered tetragonal iron (Fe) are investigated by using Monte Carlo (MC) simulations. Pairwise interactions between carbon atoms are obtained by combining the linear elasticity theory and the state-of-the-art results from density functional theory (DFT). This energy database is applied to MC simulations to predict the equilibrium carbon configuration and the collective kinetic motion of carbon atoms in an as-quenched martensite. From the metropolis MC simulation, we obtain a novel equilibrium phase of Fe 6 C 2 structure. However, according to the kinetic MC simulations, it is difficult to reach this equilibrium phase during the martensite ageing because, at room temperature or below, the carbon diffusivity is so slow that it will take an unrealistically long time for the system to achieve the equilibrium; and at higher temperature, even though the kinetics are accelerated, the carbon concentration of the predicted equilibrium phase is so high that other metastable carbides can be formed before such equilibrium is reached. Moreover, the effects of the temperature, the applied stress, and the initial state on the ageing kinetics are highlighted. The evolution of the carbon cluster concentration and the time scale of the ageing kinetics are in good agreement with some existing experimental results. Graphical abstract: